(Re)construção do princípio da dignidade da pessoa humana e direito como integridade à luz do pensamento de Ronald Dworkin - Sousa, Renan Melo de (2018)
The dissertation we present has as the main subjectdignity of the human person. Itwill be discussed, first of all, the historical constitution of the term and the corresponding axiom, as well as its role in the models of State. We will start from the roots of the principle of the dignity of the human person and begin to investigate the way in which its content and application are conceived nowadays. Then it will be pointed out the main theoretical axis of this dissertation, which is the thought of Ronald Dworkin and his theory of Law as integrity.This teorydeals with Law as an interpretive practice, cohesive and aimed at building a society of principles. We will take the ―principles of dignity‖ (self-respect and authenticity) proposed by Dworkin to form the core of the dignity of the human person. It is intended, therefore, to integrate Dworkian teachings with other equally valuable premises, corresponding to the systemic constructionism of Professor Marcio Pugliesi, as well as to the theory of communicative action of Jürgen Habermas, in order to point the need for continuous construction of the rights arising from dignity of human person. On the other hand, the perspective of the Law as integrity points to the interpretation and application of the principle of the dignity of the human person, with with the purpose of making the axiom possible. The objectiveof this dissertation is to examine the historical basis of the dignity of the human person, to present the hard core of the dignity of the human person, and to propose a cohesive model of interpretation and application whichwelcomes socialy constructed and emanated values, without, however, extrapolating the functions of those who operate the Law